Assessment of immigration law enforcement presence in a teaching hospital along the US/Mexico border - Claire Lamneck; Alexander Alvarez; Cazandra Zaragoza; Rombod Rahimian; Mario Jesus Trejo; Patricia Lebensohn (BMC, 2023)
Abstract Background Over the past decade, the United States (US) has seen a spike in migration across the US-Mexico border with an increase in hospital admissions of migrants and asylum-seekers under the custody of immigration law enforcement (ILE). This study aimed to determine how the presence of ILE officials affects patient care and provider experience in a teaching hospital setting. Methods This cross-sectional online survey solicited quantitative and qualitative feedback from medical students, residents, and attending physicians (n = 1364) at a teaching hospital system with two campuses in Arizona. The survey included participant demographics and addressed participants' experience caring for patients in ILE custody, including the perception of respect, violations of patients' privacy and autonomy, and the comfort level with understanding hospital policies and patient rights. Thematic analyses were also performed based on respondent comments. Results 332 individuals (24%) responded to the survey. Quantitative analyses revealed that 14% of participants described disrespectful behaviors of ILE officials, mainly toward detained patients. Qualitative thematic analyses of respondent comments revealed details on such disrespectful encounters including ILE officers violating the Health Insurance Portability and Accountability Act (HIPAA) and using intimidation tactics with patients. Nearly half of the respondents did not have knowledge of policies about ILE detainees' medical care, detainees' privacy rights, or ILE's authority in patient care. Conclusions This study points out the complexities, challenges, and ethical considerations of caring for patients in ILE custody in the hospital setting and the need to educate healthcare professionals on both patient and provider rights. It describes the lived experiences and difficulties that providers on the border face in trying to achieve equity in the care they provide to detained migrant patients.